“A.B.C.” of Immunotherapy in Hematological Malignancies…Promise and Perils - Jyoti Bajpai; Deepa Susan Joy Philip (Indian Journal of Medical and Paediatric Oncology)
The treatment landscape of hematological malignancies has been evolving at an extremely fast pace. Hematological malignancies are diverse and distinct from solid tumors. These constitute challenges, which are also unique opportunities for immunotherapy. The five categories of immunotherapies that have found success in the management of hematological malignancies are allogeneic hematopoietic stem cell transplant, monoclonal antibodies and innovative designs, immune checkpoint inhibitors, chimeric antigen receptor (CAR) T cells, and B cell targeting small immunomodulatory molecules. Allogeneic stem cell transplant rightly called our bluntest weapon is the oldest form of successful immunotherapy. Alternate donor transplants and improvement in supportive care have improved the scope of this immunotherapy option. Among monoclonal antibodies, rituximab forms the prototype on which over a dozen other antibodies have been developed. The bispecific T-cell engager (BiTE) blinatumomab engages cytotoxic CD3 T cells with CD19 acute lymphoblastic leukemia (ALL) cells, which is an effective treatment method for relapsed refractory ALL. Immune checkpoint inhibitors have established their role in hematological malignancies with high PD-L1 expression, including relapsed refractory Hodgkin's lymphoma and primary mediastinal B cell lymphoma (BCL). Small immunomodulatory drugs targeting the B cell receptor downstream signaling through BTK inhibitors, SYK inhibitors, PI3K inhibitors (idelalisib), and BCL-2 inhibitors (venetoclax), and immunomodulatory imide drugs (lenalidomide) have also emerged as exciting therapeutic avenues in immunotherapy. CAR T cells are one of the most exciting and promising forms of adoptive immunotherapy. CAR T cells are rightly called living drugs or serial killers to keep patients alive. CAR T cells are genetically engineered, autologous T cells that combine the cytotoxicity of T cells with the antigen-binding specificity of CARs. CARs are antigen-specific but major histocompatibility complex/human leukocyte antigen-independent. There are five approved CAR T cell products for the management of relapsed refractory leukemias, lymphoma, and multiple myeloma. The past and present of immunotherapy have been really exciting and the future looks incredibly promising. The challenges include widening the availability and affordability beyond specialized centers, identification of potentially predictive biomarkers of response, and experience in the management of complications of these novel agents. The combinational approach of multiple immunotherapies might be the way forward to complement the treatment strategies to harness the immune system and to improve survival with good quality of life.